Evolving Expressions: Modernization of Tribal Wall Paintings in West Bengal and its Adjoining States - Majumder, Arup; Dutta, Sarnali (Annals of Human and Social Sciences, 2025)
This study explores how tribal wall painting traditions are changing in West Bengal and nearby states, focusing on modernisation's effect on these art forms. The captivating area of West Bengal in India is home to forty tribal groups. Their native art shows a deep history, rich culture, and great creativity. They decorate their house walls to celebrate various festivals and events. Using ethnographic techniques, this research examines how global connections, new materials and technologies have an impact on the methods, subjects, and cultural significance of tribal wall art. The research uncovered a move away from old-school methods and themes toward up-to-date styles shaped by outside influences. To preserve tribal wall art, it's essential to grasp the cultural importance and background of the artwork, encourage local artists, and advocate for sustainable methods. This involves presenting art via documentation, exhibitions, and uplifting tribal communities through education and opportunities for income generation.